Particles and Fields 2002
DOI: 10.1142/9789812777317_0001
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative Field Theories and (Super)string Field Theories

Abstract: In this lecture notes we explain and discuss some ideas concerning noncommutative geometry in general, as well as noncommutative field theories and string field theories. We consider noncommutative quantum field theories emphasizing an issue of their renormalizability and the UV/IR mixing. Sen's conjectures on open string tachyon condensation and their application to the D-brane physics have led to wide investigations of the covariant string field theory proposed by Witten about 15 years ago. We review main in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 218 publications
(267 reference statements)
0
85
0
3
Order By: Relevance
“…In this formalism there are no problems of collisions, since while the interaction vertex comes with a Y −2 factor, the propagator comes with a factor of its inverse, which is well defined. These operators are canceled in pairs and scattering amplitudes can be calculated and give (at least on-shell and for tree diagrams) the expected results [9]. The two different choices define two a-priori inequivalent theories.…”
Section: 3)mentioning
confidence: 97%
See 1 more Smart Citation
“…In this formalism there are no problems of collisions, since while the interaction vertex comes with a Y −2 factor, the propagator comes with a factor of its inverse, which is well defined. These operators are canceled in pairs and scattering amplitudes can be calculated and give (at least on-shell and for tree diagrams) the expected results [9]. The two different choices define two a-priori inequivalent theories.…”
Section: 3)mentioning
confidence: 97%
“…In fact, a solution based on this vertex operator (in the theory with chiral Y −2 ) was found using lowest-level truncation in [30], where it was interpreted as a supersymmetry breaking solution. In AGM it was suggested that the correct resolution of these problems is to define the string field on the non-BPS D-brane using a gauge field with Erler's gauge field in the GSO(+) sector 2 and with 9) in the GSO(−) sector. It is immediate that the action is the same as in Erler's case.…”
Section: On the Non-bps D-branementioning
confidence: 99%
“…The unique (up to rescaling of fields) gauge invariant action unifying the GSO(+) and GSO(−) sectors is [8] (for notations see review [26])…”
Section: Set Upmentioning
confidence: 99%
“…Several papers have explicitly shown that such theories as φ 4 and U(N) gauge theories, when formulated on a non-commutative space, are one loop renormalizable [5,6,7,8,9,10]. However, results in the literature [11] have shown that non-commutativity renders impossible the continuum renormalization of the spontaneously broken linear sigma model.…”
Section: Introductionmentioning
confidence: 99%